Avoidance Reduction Therapy for School-Age Children Who Stutter - Sisskin, Vivian; Goldstein, Benjamin (Seminars in Speech and Language, 2022)
Avoidance Reduction Therapy for Stuttering (ARTS) is a behavioral therapy for children and adults that incorporates speech therapy and counseling to reduce learned physical and socioemotional struggle that constitute the problem for the stutterer.a While stuttering is a neurodevelopmental difference, efforts to mask a stigmatized identity can contribute to avoidance, shame, and fear of speaking. This article provides theoretical foundations for therapy principles, describes the processes of self-acceptance and change, and outlines therapy goals and activities using child-friendly explanations and case study vignettes.
Keywords: stuttering; acceptance; avoidance reduction; children; therapy